Flour derived porous carbon as anode for highly robust potassium-ion batteries - Liu, Yong; Gong, Zhen; Li, Liqing (Frontiers in Energy Research, 2022)
Potassium-ion batteries (PIBs) have attracted increasing research interest because of the natural abundance and low cost of potassium. Nevertheless, lacking of suitable anode materials that can deliver high reversible capacity and long cycle life highly hinder the further development of PIBs. Here, we report a flour chemistry strategy to establish a porous phosphorus-doped carbon (PPDC) as anode for high-performance PIBs. The as-prepared PPDC with high hierarchically porous structure and rich P-doping not only offers fast transport of K+ and electrons during continuous cycling, but also affords sufficient inner space to relieve volume expansion of active electrode. Therefore, the PPDC displayed high reversible capacity, excellent cyclic stability, outstanding rate performance. These results imply a great potential for applications in the field of high-energy storage devices.